An oil-free linear compressor for use with compact heat exchangers - Bailey, P; Dadd, M; Stone, C (2009)
There are a number of applications emerging where it is desirable to extract large amounts of heat from relatively small surfaces. An example is the requirement for new computer processors. One approach is to use vapour cycle refrigeration circuits with evaporators that have miniaturised heat exchange surfaces. Although it would be desirable to build such an evaporator into a refrigeration circuit that uses conventional components, this is not practicable using existing oil lubricated compressors. The development of a novel low cost oil-free compressor is described. This unit is based on successful oil-free technology used in space refrigeration applications. © IMechE, 2009.